Prospective assessment of fatigue and health status in Greek patients with breast cancer undergoing adjuvant radiotherapy - Lavdaniti, Maria; Patiraki, Elisabeth; Dafni, Urania; Katapodi, Maria; Papathanassoglou, Elizabeth; Sotiropoulou, Anastasia (My University, 2006)
Purpose/Objectives: To describe fatigue in women with breast cancer undergoing radiotherapy and to explore the impact of fatigue on their health status. Design: Prospective, descriptive, repeated measures. Setting: A major oncology center, Saint Savvas Cancer Hospital, in Athens, Greece. Sample: Consecutive sample of 106 women (mean age = 55 ± 12), with histologically confirmed diagnosis for stage I or II breast cancer who were receiving adjuvant radiotherapy for approximately six weeks. Methods: Data were collected with the Revised Piper Fatigue Scale (PFS) and the Short Form-36 (SF-36) Health Survey Scale in the first two days of radiotherapy (T 0), during the third week (T 1), and during the last week of treatment (T 2). Main Research Variables: Fatigue, health status. Findings: Across-subjects analysis revealed that fatigue increased during radiotherapy in patients with breast cancer regardless of stage, type of surgery, or whether they received chemotherapy (p < 0.05). Between-subject analysis revealed that no differences existed in the PFS between different groups (chemotherapy versus no chemotherapy, breast conservation versus mastectomy, stage I versus stage II) at each measurement point. A negative correlation was found between the subscales of the PFS and all of the subscales of the SF-36. Conclusions: Fatigue intensity increased significantly during the course of radiotherapy, and patients experienced a significant deterioration in their overall health status. Implications for Nursing: Findings contribute to the growing body of evidence regarding fatigue and its impact on health status in Greek patients with breast cancer and provide insights for effective nursing assessment, patient education, and symptom management.
Keywords: Adjuvant therapy; Breast tumor; Fatigue; Health status; Middle aged; Prospective study